Implementasi Fungsi Administrasi Dakwah Pesantren Pasal 39 Undang-undang no.18 Tahun 2019 di Pondok Pesantren Darus-Sunnah Ciputat - Mohamad Yasir Arfan; Rahmat Salam; Izzatusholekha (Program Pascasarjana IIQ Jakarta, 2024)
This research discuss the implementation of the da'wah administration function carried out by the Darus-Sunnah Ciputat Islamic boarding school based on article 39 of Law No.18/2019, based on data from the Indonesian Ministry of Religion; The number of Islamic boarding schools throughout Indonesia has statistically reached around 39,220. However, the process of implementing the missionary function carried out by Islamic boarding schools is faced with obstacles and challenges ranging from good planning, direction to implementation. Referring to William H. Newman's theory through 7 (seven) general administrative function processes consisting of: planning, organizing, coordinating, reporting, budgeting, staffing, and directing. Want to measure how the implementation of the da'wah administration function is carried out. The type of research used is qualitative research with a descriptive method, namely trying to explain problem solving using available data through interviews, observation and documentation studies. Based on the analysis, the results obtained from the research and discussion show that the implementation of the da'wah administration function carried out by the Darus-Sunnah Islamic boarding school through seven administrative function processes has been running quite optimally, but with continuous efforts to improve the shortcomings of these administrative function processes.